Substance use during pregnancy and risk of postpartum depression: a systematic review and meta-analysis - Pacho, Malein; Aymerich, Claudia; Pedruzo, Borja; Salazar de Pablo, Gonzalo; Sesma, Eva; Bordenave, Marta; Dieguez, Rodrigo; Lopez-Zorroza, Itziar; Herrero, Jon; Laborda, Maria; Fernandez-Rivas, Aranzazu; Garcia-Rizo, Clemente; et al. (Frontiers in Psychiatry, 2023)
Introduction: Postpartum depression (PPD) is a prevalent mental health condition affecting women globally within the first year following childbirth. Substance use during pregnancy has been associated with an increased risk of developing PPD, but the evidence remains inconclusive. This meta-analysis aims to comprehensively assess the effects of different substances on PPD risk, exploring potential modifiers and confounding factors. Objectives: To examine the proportion of PPD among substance users during pregnancy, compared to non-users, and investigate the specific risk associated with different substances (tobacco, alcohol, and non-specified substance use/multiple substance use).Methods: A systematic literature search was conducted from inception to November 2022 using the Web of Science database (Clarivate Analytics), incorporating Web of Science Core Collection, the BIOSIS Citation Index, the KCI-Korean Journal Database, MEDLINE®, the Russian Science Citation Index, the SciELO Citation Index, and the Cochrane Central Register of Reviews, and Ovid/PsycINFO databases. Inclusion criteria comprised original studies with pregnant women, using validated depression scales and substance use reporting. Results: Among the 26 included studies, encompassing 514,441 women, the pooled prevalence of PPD among substance users during pregnancy was 29% (95% CI 25 -33). Meta-analyses revealed an overall odds ratio (OR) of 3.67 (95% CI 2.31 -5.85; p<0.01) indicating a significantly higher risk of PPD among substance users compared to non-users.Subgroup analyses demonstrated a higher risk for women with non-specified or multiple substance use (OR 4.67, p<0.01) and, tobacco use (OR 4.01, p<0.01).Alcohol use showed a trend toward higher risk that did not reach statistical significance , but no significant difference for alcohol users (OR 1.88, p=0.051). Conclusions: This meta-analysis provides evidence of an increased risk of PPD among pregnant substance users, particularly those using multiple substances or tobacco. However, caution is needed in interpreting the association with alcohol use due to its non-significant result.